INTERNATIONAL CLASSIFICATION OF FUNCTIONING, DISABILITY AND HEALTH: ADULTS WITH VISUAL IMPAIRMENT (Годишен зборник на Филозофски факултет - Скопје, 2023)
The purpose of this paper is to present an overview of current studies on the general limitations of using the International Classification of Functioning, Disability and Health (ICF), as well as to review the results of its application in adults with visual impairment. The literature search was performed in ERIC, EBSCO-Host, ScienceDirect, PROKUEST, SCOPUS, and Google Scholar. Articles were selected if they reported on any of the strengths and weaknesses of the ICF, also its application to adults with visual impairment. The literature review was performed using the PRISMA criteria. The search of relevant literature revealed 8 articles that met the eligibility criteria. The overall conclusion is that while the ICF is a valuable tool for describing how a person functions, it is not an evaluation instrument in itself.